Enhancement of performance and sulfur resistance of Si-doped V/W/Ti using sulfation for selective catalytic reduction of NOx with ammonia. Issue 5 (23rd February 2023) - Won, Jong Min; Kim, Min Su; Hong, Sung Chang
ABSTRACT: This study investigated the SO2 resistance enhancement factors of silica with the V/SiW/TiO2 catalyst prepared using various precursors. BET, XPS, H2 -TPR, DRIFT, and temperature-programmed desorption (TPD) were used to analyze the physical and chemical properties of the catalyst. The catalyst prepared with Dimethoxydimethylsilane (DMDMS), from various precursor silica fabricated to improve SO2 resistance, demonstrated the highest increase in resistance. The SO2 resistance improvement factor was confirmed to form Si 2+ (Si-O-Ti) species in the optimised V/SiW/TiO2 catalyst; the incoming SO2 was converted to Si(SO4 ). The formation of Si(SO4 ) increased the number of adsorbed sites for adsorbed NH3, in the form of SO4 -NH3 to increase the amount of the reducing agent of NH3 -SCR, and improve denitrification efficiency. It was optimal to increase the VOx surface density whilst increasing the ratio of the Si 2+ species, the Si-sulfate site of SiW/TiO2 support, to improve denitrification performance and SO2 resistance concurrently. Highlights: The SO2 resistance improvement factor was confirmed to form Si 2+ (Si-O-Ti) species. In the optimised V/SiW/TiO2 catalyst; the incoming SO2 was converted to Si(SO4 ). The formation of Si(SO4 ) increased active sites for adsorbed NH3, in the form of SO4 -NH3 to improve denitrification efficiency. GRAPHICAL ABSTRACT: UF0001